PENGARUH KETIDAKAMANAN KERJA TERHADAP KEPUASAN KERJA DIMEDIASI STRES KERJA FREELANCER DI KOTA DENPASAR (STUDI KASUS: GEN Z) - Putri, Nadia Priscilla; Ni Nyoman Sudiyani; I Gusti Putu Agung Widya Goca (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2025)
This study seeks to examine the impact of job insecurity on job satisfaction, with work stress serving as a mediating variable, among Generation Z freelancers in Denpasar City. This research is driven by the reduction in the freelancer population in the region from 269,422 in 2020 to 18,776 in 2024, highlighting considerable obstacles to attaining employment satisfaction. The primary issue examined is the impact of job insecurity and work-related stress on the job satisfaction of Gen Z freelancers in Denpasar, both independently and concurrently, as well as the role of work stress as a mediator in the relationship between job insecurity and job happiness. The population comprised 18,776 freelancers, and a sample of 100 Gen Z respondents with at least one year of work experience was selected using Slovin's methodology. Data were gathered via questionnaires and analyzed employing the Partial Least Square (PLS) approach with SmartPLS. The findings demonstrate that job insecurity exerts a positive and significant effect on job satisfaction (inversely, indicating that more job insecurity correlates with diminished job satisfaction) and also considerably heightens work- related stress. Work stress significantly impacts job satisfaction negatively, indicating that heightened work stress generally reduces job satisfaction, and it partially mediates the relationship between job insecurity and job satisfaction. These findings highlight the intricate dynamics of freelance work and the necessity of addressing job insecurity and work-related stress to promote freelancer well- being, providing essential insights for stakeholders in developing strategies to boost job satisfaction in this uncertain period.